Grain yield and associated traits of maize (Zea mays L.) genotypes in Malaysian tropical environment - Chowdhury, Golam Faruq Md Khairuzzaman; Nurul Farhana,; Zain, Mohamad Firdaus; Abdul Majid, Nazia; Rahman, M. M.; Rahman, M. Motior; Abdul Kadir, Mihdzar (Academic Journals, 2011)
Twenty two tropical composite maize (Zea mays L.) genotypes from International maize and Wheat Improvement centre (CIMMYT) were grown in randomized complete block design with two replicates to assess the correlation between yield and other traits such as 50% silking (female flowering date), 50% tasseling date (male flowering date, Ear/plant, thousand grain weight, plant height and ear height in the tropical environment of Malaysia. Grain yield correlated highest between field weight (rA = 0.59), followed by ear height (rA = 0.50) and plant height (rA = 0.49). Positive correlations was not found between grain yield and days to 50% silking (rA = 0.17), days to 50% tasseling (rA = 0.19), ear/plant (rA = 0.26) and thousand grain weight (rA = 0.10). Negative correlation was observed between maturation date (rA = -0.025) and grain filling period (rA = -0.198). Higher values of two traits, such as plant height (R2 = 0.24) and ear height (R2 = 0.25) showed appreciably higher tend to grain yield. From linear models, days to 50% tasseling (R2 = 0.04) and days to 50% silking (R2 = 0.04) accounted for only 4% of the total variation in grain yield (R2 = 0.04) while the other traits accounted for as much as 96%. No linear regression found between grain yield and maturation date (R2 = 0.00). But there were linear regressions between grain yield and ear / plant (R2 = 0.056), field weight (R2 = 0.361) and 1000 grain weight (R2 = 0.02) in proportion of 5.6, 36.1 and 2% of grain yield, respectively. Negative linear regression was observed between grain yield and grain filling period ((R2 =0.036). Field weight, ear height, and plant height and shell percentage have the highest correlation with grain yield that were determine by the yield of twenty two tropical composite maize (Z. mays L.). The present findings might be useful to the breeders to select the potential parental materials for maize improvement program in tropical Malaysia.